2015
DOI: 10.1128/aem.03389-14
|View full text |Cite
|
Sign up to set email alerts
|

New Mode of Energy Metabolism in the Seventh Order of Methanogens as Revealed by Comparative Genome Analysis of “Candidatus Methanoplasma termitum”

Abstract: The recently discovered seventh order of methanogens, the Methanomassiliicoccales (previously referred to as "Methanoplasmatales"), so far consists exclusively of obligately hydrogen-dependent methylotrophs. We sequenced the complete genome of "Candidatus Methanoplasma termitum" from a highly enriched culture obtained from the intestinal tract of termites and compared it with the previously published genomes of three other strains from the human gut, including the first isolate of the order. Like all other str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
264
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(282 citation statements)
references
References 93 publications
15
264
1
2
Order By: Relevance
“…Methanogenic archaea are widespread in nature and have been detected in a diverse range of environments including wetlands, rice agriculture, landfills, hydrothermal vents, ruminants and termites 1,2 . Traditionally, all methanogens belonged to the archaeal phylum Euryarchaeota and until recently were classified into seven orders 1,3,5 (Methanobacteriales, Methanococcales, Methanomicrobiales, Methanosarcinales, Methanocellales, Methanopyrales and Methanomassiliicoccales). Substrates for methane production include H 2 /CO 2 (hydrogenotrophic), acetate (acetoclastic) and methylated compounds (methylotrophic) 5 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Methanogenic archaea are widespread in nature and have been detected in a diverse range of environments including wetlands, rice agriculture, landfills, hydrothermal vents, ruminants and termites 1,2 . Traditionally, all methanogens belonged to the archaeal phylum Euryarchaeota and until recently were classified into seven orders 1,3,5 (Methanobacteriales, Methanococcales, Methanomicrobiales, Methanosarcinales, Methanocellales, Methanopyrales and Methanomassiliicoccales). Substrates for methane production include H 2 /CO 2 (hydrogenotrophic), acetate (acetoclastic) and methylated compounds (methylotrophic) 5 .…”
mentioning
confidence: 99%
“…Traditionally, all methanogens belonged to the archaeal phylum Euryarchaeota and until recently were classified into seven orders 1,3,5 (Methanobacteriales, Methanococcales, Methanomicrobiales, Methanosarcinales, Methanocellales, Methanopyrales and Methanomassiliicoccales). Substrates for methane production include H 2 /CO 2 (hydrogenotrophic), acetate (acetoclastic) and methylated compounds (methylotrophic) 5 . Hydrogenotrophic methanogenesis is the most widespread 1 , being found in all methanogenic orders with the exception of Methanomassiliicoccales, and it has been suggested that this is the ancestral form of methane production 6 .…”
mentioning
confidence: 99%
See 3 more Smart Citations